Recent Advances of Volatile Memristors: Devices, Mechanisms, and Applications. (8th July 2020) - Wang, Ruopeng; Yang, Jia-Qin; Mao, Jing-Yu; Wang, Zhan-Peng; Wu, Shuang; Zhou, Maojie; Chen, Tianyi; Zhou, Ye; Han, Su-Ting
Abstract : Due to the rapid development of artificial intelligence (AI) and internet of things (IoTs), neuromorphic computing and hardware security are becoming more and more important. The volatile memristors, which feature spontaneous decay of device conductance, own the distinct combination of high similarity to the biological neurons and synapses and unique physical mechanisms. They are excellent candidates for mimicking the synaptic functions and ideal randomness source of the entropy for hardware‐based security. Herein, the recent advances of volatile memristors in devices, mechanisms, and application aspects are summarized. First, a brief introduction is presented to describe the switching type, materials, and temporal response of volatile memristors. Second, the volatile switching mechanisms are discussed and grouped into ion effects, thermal effects, and electrical effects. Third, attention is focused on the applications of volatile memristors for access devices, neuromorphic computing (artificial neurons and synapses), and hardware security (true random number generators and physical unclonable functions). Finally, major challenges and future outlook of volatile memristors for neuromorphic computing and hardware security are discussed. Abstract : The volatile memristors, featuring spontaneous conductance decay, are consisted by metal–insulator–metal sandwiched structure. With unique characteristics of high similarity to the biological nervous system and physical mechanisms, they are regarded as the ideal randomness sources of the entropy for hardware security and good candidates for mimicking synaptic functions.